The Effectiveness of Play Therapy: Coloring Against Anxiety Reduction in Pre-School Children Who Experience Hospitalization - Nurjanah, Suci; Santoso, Shelfi Dwi Retnani Putri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Hospitalization for children has long-term and short-term impacts. The short-term is fear and anxiety, and if do not treat immediately, the children will deny the care and treatment. The other short-term impacts are insomnia, crying and afraid of the health team, so they deny the treatment given, which will affect the length of stay, aggravate the condition and even cause death. Anxiety causes physiological responses such as changes in the cardiovascular system and gasping breath patterns. Fear and anxiety are disturbances in the emotional needs of children, which requires treatment immediately because it affects their growth and development. The research design used was a quasi-experimental design with "one group pre and post-test with control group design". This research used a purposive sampling technique with the number of respondents being 40 people, 20 respondents were given a play therapy intervention, and 20 respondents were in the control group. The research results showed an effect of colouring play therapy on the anxiety level of hospitalized children with a p-value = 0.000 less than 0.05. Conclusion: Coloring play therapy is effective in reducing the anxiety of hospitalized pre-school children. Recommendation: improving the playing equipment facilities in hospitals and making play therapy a continuous activity for treatment and nursing interventions.Hospitalisasi pada anak memiliki dampak jangka panjang dan dampak jangka pendek. Dampak jangka pendek berupa ketakutan dan kecemasan sehingga bila tidak ditangani segera anak akan melakukan penolakan terhadap perawatan dan pengobatan yang akan diberikan, selain itu dampak jangka pendek yang mungkin muncul adalah susah tidur, menangis dan takut dengan tim kesehatan sehingga anak menolak tindakan perawatan yang diberikan kepada anak, hal ini akan berpengaruh terhadap lamanya hari rawat, memberat kondisi anak dan menyebabkan kematian,  kecemasan akan menimbulkan respon fisiologis yakni perubahan sistim kardiovaskuler dan perubahan pola nafas yang terengah-engah. Ketakutan dan kecemasan merupakan gangguan terhadap terpenuhinya kebutuhan emosional anak, yang diperlukan penanganan sesegera mungkin karena berdampak pada pertumbuhan den perkembangan. Desain penelitian yang digunakan dalam penelitian ini adalah Quasi experiment dengan rancangan “one group pre and post test with control group design”. Pada penelitian ini mengunakan tehnik Purposive sampling dengan jumlah responden 40 orang, 20 resonden diberikan intervensi Play Therapi mewarni dan 20 responden kelompok kontrol. Ada pengaruh play therapi mewarnai terhadap tingkat kecemasan anak yang mengalami hospitalisasi dengan P value = 0,000 kurang dari 0,05. Play therapy merawani efektif dalam menurunkan kecemasan anak pra sekolah yang mengalai hospitalisasi. Meningkatan fasilitas alat pemaianan di rumah sakit serta menjadikan play therapy sebagai kegiatan berkelajutan untuk pengobatan dan intervensi keperawatan.